Bauran Promosi Jasa Kebersihan PT X untuk Wilayah Jakarta - Badingah, Tolingatul; Widiawati, Kristiana (JURNAL MAHASISWA BINA INSANI; Vol 8 No 1 (2023): Jurnal Mahasiswa Bina Insani (Agustus 2023), 2023)
The cleaning services industry in Indonesia has a high level of competition because of the large number of service providers in this field. Every company must develop a sales strategy to maintain its business in the face of competition. Promotional mix is the right strategy to introduce services, attract customer interest and increase demand for services. The research method used is descriptive qualitative research by conducting interviews with Business Consultants at PT X to obtain primary data and observation to obtain secondary data. Based on the results of research analysis, the promotional mix implemented by PT X is advertising, public relations, personal selling and direct marketing. Meanwhile, the promotional mix that has not been implemented is sales promotion. The findings and obstacles based on the research results are that advertising via social media Instagram and TikTok has not been actively implemented. Referring to the findings, the proposal given is to increase advertising via Instagram by creating Q&A (Question & Answer) on Instagram Stories and creating content in the form of TikTok videos.